Феномен незнания, или Кое-что о просвещенном невежестве - Суименко, Е. (Социология: теория, методы, маркетинг, 1999)
The author contends that there are two kinds of lack of knowledge: scientific problemand ignorance. Last one can develop from primitive and naive mythology to refined ignorance looking like science (educated ignorance). It has deep social and cultural roots. Lack of knowledge can be constructive and functional in society, while ignorance is always destructive. In author’s opinion, lack of knowledge could make progress, as far as possible, if it would get rid of ignorance.